Recent progress on polyvinyl alcohol-based materials for energy conversion. (25th January 2022) - Qiao, Zhiyong; Ding, Changming
Abstract : The recent progress in PVA-based materials for electrocatalytic energy conversion has been summarized. Abstract : Electrocatalytic energy conversion shows a promising "bridge" to mitigate energy shortage issue and minimizes ecological implications through synergy with sustainable energy sources, which calls for low-cost, highly active, and durable electrocatalysts. Recent research studies have revealed that polyvinyl alcohol (PVA)-based materials are emerging as potential electrocatalysts for boosting electrocatalytic energy conversion due to their high electronic conductivity, excellent mechanical and chemical stability. Aiming to gain a better understanding of the advantages and applications of PVA in the field of electrocatalytic energy conversion, this review systematically summarizes the recent progress of PVA-based materials achieved in the field of electrocatalytic energy conversion. We start by discussing the distinct advantages of PVA for electrochemical reactions. Next, the experimental progress on investigating the multifunctionalities of PVA-based materials for energy conversion is illustrated. Finally, the challenging issues that need to be addressed before realizing the commercial applications are also discussed, hoping to offer guidance for the construction of more efficient PVA-based electrode materials.